2019
DOI: 10.12998/wjcc.v7.i9.1028
|View full text |Cite
|
Sign up to set email alerts
|

Causes associated with recurrent choledocholithiasis following therapeutic endoscopic retrograde cholangiopancreatography: A large sample sized retrospective study

Abstract: BACKGROUND Recurrence of primary choledocholithiasis commonly occurs after complete removal of stones by therapeutic endoscopic retrograde cholangiopancreatography (ERCP). The potential causes of the recurrence of choledocholithiasis after ERCP are unclear. AIM To analyze the potential causes of the recurrence of choledocholithiasis after ERCP. METHODS The ERCP database of our medical center for the period between January 2007 and January 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 29 publications
6
33
0
Order By: Relevance
“…Feng Deng et al (19) found that the diameter of choledocholithiasis ≥10 mm was an independent risk factor for the recurrence of choledocholithiasis after ERCP. The larger the stone diameter, the larger the bile duct dilatation.…”
Section: Size and Number Of Stonesmentioning
confidence: 99%
See 4 more Smart Citations
“…Feng Deng et al (19) found that the diameter of choledocholithiasis ≥10 mm was an independent risk factor for the recurrence of choledocholithiasis after ERCP. The larger the stone diameter, the larger the bile duct dilatation.…”
Section: Size and Number Of Stonesmentioning
confidence: 99%
“…67Although it has been confirmed that the diameter of common bile duct is a risk factor for the recurrence, the specific diameter has not yet been determined. Deng (19) and Park (65) believed 10mm, but Song (77) and Yoo (96) believe that the diameter of common bile duct≥15mm is a potential predictor after endoscopic stoning. It is worth mentioning that Jeon Jin et al (31) found that there is an inverse relationship between restoration of CBD diameter within two weeks and CBD stone recurrence.…”
Section: Diameter Of Common Bile Ductmentioning
confidence: 99%
See 3 more Smart Citations